Rémanence de Madame Bovary dans l’édition illustrée - Bruno Gallice (Flaubert: Revue Critique et Génétique)
This article focuses on the illustrated editions of Madame Bovary. After Flaubert’s death these editions were popular and multiplied until the end of the 1850’s. They represent a testimony of the novel’s reception by illustrators. After diachronic considerations about the increasing importance of the novel’s illustration, we study the way images treated the characters, between graphic fixation and emancipation. Artists claimed for themselves Emma Bovary in particular, and constantly updated their vision of Flaubert’s character, who became for the reader a figure both permeable and vivid.